Making and becoming the Undocumented and the Illegal: Discourses of immigration and American higher education policy - Ryan Evely Gildersleeve (Arizona State University, 2017)
This paper discursively analyzes the public conversation around immigration as it intra-sects with state and federal policy, particularly in relation to higher education. I take in-state resident tuition policy as a departure point for an interpretive effort to explain how "undocumented" and "illegal" subject positions are produced through intra-secting policy texts, popular journalism, and presidential campaigns. I illustrate how the ethics produced through this policy regime act pedagogically, mediating understandings of students becoming reified into "undocumented" and/or "illegal" identities. I pay special attention to the discursive productions made available from policy texts, both state-based (e.g., CA Dream Act) and federal (e.g., DACA), highlighting the use of discourse analysis in the interrogation of social policy.